INVESTIGATING GRAMMAR, MECHANICS AND REGISTER ERRORS IN DIALOGUE WRITING: A DESCRIPTIVE QUALITATIVE STUDY ON COMMUNICATION SCIENCE STUDENTS AT UNIVERSITAS MUHAMMADIYAH KARANGANYAR 2024/2025 - DWI CAHYONO (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
This study investigates grammar, mechanics, and register errors in dialogue writing produced by Communication Science students at Universitas Muhammadiyah Karanganyar during the 2024–2025 academic year. Applying a descriptive qualitative design, the writing of ten student groups was analyzed to identify common error patterns and classify them into three categories: grammar, mechanics, and register. Data analysis revealed that grammar common errors included sentence fragments, awkward word choices, and incorrect verb forms. In addition, mechanical errors involved capitalization, punctuation, spelling, and inconsistent time notation. Furthermore, register issues were also frequent such as students relying on informal and social media expressions that were inappropriate for academic writing. The findings indicate that their written accuracy was often limited by weaknesses in grammar and mechanics. Many of the errors reflected direct transfer from spoken Indonesian or the influence of online communication styles. The results show that teaching writing in English as a Foreign Language should combine grammar, mechanics, and register, not treat them as separate areas. The study recommends classroom activities that combine error analysis, peer editing, and register transformation tasks to foster both accuracy and appropriacy in student writing. Those approaches may help English as a Foreign Language learners produce clearer, more professional written communication in academic settings.